Unsteady MHD heat transfer in couette flow of water at 4 [degrees] C in a rotating system with ramped temperature via finite element method - Reddy, G. Jithender; Raju, R. Srinivasa; Rao, J. Anand; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady magnetohydromagnetic natural convection on the Couette flow of electrically conducting water at 4 [degrees] C (Pr = 11.40) in a rotating system has been considered. A Finite Element Method (FEM) was employed to find the numerical solutions of the dimensionless governing coupled boundary layer partial differential equations. The primary velocity, secondary velocity and temperature of water at 4 [degrees] C as well as shear stresses and rate of heat transfer have been obtained for both ramped temperature and isothermal plates. The results are independent of the mesh (grid) size and the present numerical solutions through the Finite Element Method (FEM) are in good agreement with the existing analytical solutions by the Laplace Transform Technique (LTT). These are shown in tabular and graphical forms.
Keywords: MHD; Couette flow; heat transfer; FEM